Adequate 25(OH)D moderates the relationship between dietary inflammatory potential and cardiovascular health risk during the second trimester of pregnancy - Yin, Wan-jun; Yu, Li-jun; Wu, Lin; Zhang, Lei; Li, Qiong; Dai, Fei-cai; Tao, Rui-xue; Jiang, Xiao-min; Zhu, Peng (Frontiers in Nutrition, 2022)
Background: Pro-inflammatory diets play an important role in developing cardiovascular disease (CVD). Vitamin D has been demonstrated to have an anti-inflammatory effect and promote cardiovascular health (CVH). However, it is unclear whether adequate vitamin D during pregnancy protects against poor CVH caused by pro-inflammatory diets. Objective: To investigate the association of pro-inflammatory diets with cardiovascular risk (CVR) among pregnant women and whether such association was modified by vitamin D status. Methods: The study was based on a prospective birth cohort that included 3713 pregnant women between 16 and 23 gestational weeks. 25(OH)D concentrations and high-sensitivity C-reactive protein (hs-CRP) were measured from collected blood. The dietary inflammatory potential was evaluated using the empirical dietary inflammatory pattern (EDIP) score based on a validated food frequency questionnaire. Gestational CVR was evaluated using the CVR score based on five “clinical” CVR metrics, including body mass index, blood pressure, total cholesterol, glucose levels, and smoking status. Results: The proportion of women with CVR score > 0 was 54.3%. We observed a positive association between the EDIP score and CVR score. Compared with the lowest quartile, the CVR score ( = -0.114, 95% CI, -0.217, -0.011) and hs-CRP levels ( = -0.280, 95% CI, -0.495, -0.065) were lower in the highest quartile (P for trend < 0.05). Increased CVR connected with high EDIP score was observed only in women with 25(OH)D concentrations < 50 nmol/L (RR = 1.85; 95% CI: 1.35, 2.54). Mediation analysis revealed that the proportion of association between the EDIP score and CVR score mediated by 25(OH)D was 28.7%, and the proportion of the association between 25(OH)D and the CVR score mediated by hs-CRP was 21.9%. Conclusions: The higher dietary inflammatory potential was associated with an increased CVR during pregnancy by promoting inflammation. Adequate vitamin D could exert anti-inflammatory effects and modify such association.